SPECIFICS OF CREATIVE ACTIVITY OF A TEACHER-PSYCHOLOGIST IN THE CONDITIONS OF INTEGRATED TRAINING - Babaev, Doolotbai; Gussenova, Meiriban; Sapargaliyeva, Aizhan (Scientific Journal of Pedagogy and Economics, 2020)
The article presents the features of psychological and pedagogical support in the conditions of integrated learning. The role of a teacher - psychologist in the design and organization of psychological and pedagogical support of the educational process is considered. The main directions of psychological and pedagogical support for the development of professional competence of a teacher, the specifics of his creative activity are formulated. The main conditions for the effectiveness of programs of psychological and pedagogical support are considered. At the present stage of development in the Republic of Kazakhstan, there are deep socio-economic transformations that require new approaches to the system of vocational education. The First President of the Republic of Kazakhstan Elbasy N. A. Nazarbayev pays attention to the development of science and education in the program "100 concrete steps" in five institutional reforms. Special emphasis is placed on improving the competitiveness of graduates and the growth of the educational sector. The article considers the theoretical features of the priority tasks of higher education, strengthening the resource base, expanding the practical component of scientific and educational activities, investments in the preservation and development of human capital, which is the main priority of the State program for the development of education of the Republic of Kazakhstan for 2011 – 2020. The paper describes the need for specialists who can productively organize interaction and relationship in the "person-to-person" system. In these conditions, the problems of training specialists in the so-called "helping professions" (psychologists, social workers, etc.) become urgent. The article describes the current socio-economic situation in Kazakhstan, which also determines the order for specialists of this profile who have the qualities and skills of activity in this field, which requires the modernization of training students in the relevant specialties of the higher education system. Both domestic and foreign experts are increasingly calling the XXI century the century of "man". The article considers that in modern socio-economic conditions, the problem of developing creative abilities remains one of the most important problems of human society. It is particularly relevant in modern society, because education as a resource of science, technology and art is undergoing radical changes today, due to the need for continuous adaptation to rapidly changing dynamic socio-economic conditions. In addition, the paper describes the fact that this is due to the constantly increasing volume of information, which is forced to operate a modern specialist in any field, and the process of integrating the Sciences, which requires a person not only extensive knowledge, but also a higher creative level of thinking development.